Trade openness, exchange rate, gross domestic investment, and growth in Indonesia - Yusoff, Mohammed; ., Ilza Febrina (2012)
This study examines the relationships among economic growth, domestic investment, real exchange rate, and trade openness in Indonesia. We carried out the unit root test, the Johansen co-integration test and then estimated the VEC model. The results suggest that there exists a long-run relationship among the variables. All the estimated coefficients of the long run equation have the correct positive signs and significant at least at 5 percent level. Specifically, a one percent increase in trade openness leads to about 26.5 percent increase in Indonesian real GDP in the long-run; a one percent increase in domestic investment will spur GDP by 1.8 percent, and a one percent depreciation of rupiah promotes GDP by about 6.4 percent in the long-run. The results of Granger causality test using VECM suggest that all the variables cause real GDP in the short-run. Both the trade openness and gross domestic investment cause growth unidirectionally in short-run, except for real exchange rate. The evidence suggests that trade openness, GDI and exchange rate are important determinants of economic growth. And therefore policy makers should seriously take these variables into account in their policy construct in order to sustain economic growth in Indonesia. Specifically, Indonesia should promote foreign trade, improve the domestic investment climate, and maintain exchange rate stability.